Le Chiese orientali cattoliche nel movimento Ecumenico - Lorenzo, Lorusso (Iustitia, 2016)
Fr. Lorusso Lorenzo treats the role of the Oriental Churches in the ecumenical movement. Eastern Catholic Churches' "special function in fostering unity among all Eastern Churches" (CCEO c. 903) derives from the fact that the oriental Churches, catholic and orthodox, have centuries old common history and tradition as well as a common ecclesial sense" (p. 4). He discusses the title XVIII of CCEO connecting them with their sources as well as other relevant canons of the code. He claims that the progress of the dialogue between the Orthodox Church and the Catholic Church (Church of Rome), at the universal level, will depend on the dialogue between the orthodox and catholic local Churches.